On Finding the Coefficients of the Ehrhart Polynomials c d 9 of a Polyhedron in d - Khaleel, Ahlam J; Al-Najjar, Shatha A (Al-Nahrain Journal of Science, 2012)
Computing the volume and integral points of a polyhedron in is a very important subject in different areas of mathematics, such as: number theory, toric Hilbert functions, Kostant's partition function in representation theory, Ehrhart polynomial in combinatorics, cryptography, integer programming, statistical contingency and mass spectroscope analysis .Therefore a method for finding the coefficients of this polynomial are to be listed. A program in visual basic language is made for finding the general differentiation of the function that are used for finding the coefficients of the Ehrhart polynomials.